Analysis of Legal Positivism Theory in Murder Cases: The Role of Evidence, The Objective-Empirical Relationship, and The Influence of Moral Values - Valiantnuja Washfaa Yunandeva (Universitas Muhammadiyah Surakarta, 2024)
The purpose of this writing is to find out how to analyze murder cases based on the theory of legal positivism. Using qualitative research methods. The results and discussion show that the theory of legal positivism plays a central role in the analysis of murder cases by emphasizing objective and empirical aspects. In this context, evidence and facts have a crucial role in determining the guilt or innocence of the defendant. Law enforcement in murder cases is influenced by an approach based on empirical realities that can be measured and identified objectively. Moral and ethical aspects, although they may be relevant in social contexts, do not receive primary emphasis in legal analysis based on positivist theory. Instead, the assessment of criminal acts is more inclined towards facts, rather than considerations of moral values. Thus, legal positivism theory provides a strong foundation for the analysis of murder cases by prioritizing a more objective and empirical approach.